Heretycki szał czy recepcja cesarskiego prawodawstwa w polityce religijnej królów wandalskich? Codex Theodosianus XVI a Edictum Hunirici - Wilczyński, Marek (Vox Patrum, 2020)
The knowledge about the religious policy of the Vandal kings is provided only by the sources which are hostile toward the Vandals, written by the followers of the Nicene orthodoxy. The Arianic sources from this period, even if they existed, have not survived. The preserved sources focus on persecutions – usually drastic in form – and the imposition of Arian heresy by force. According to the authors of the sources, the ferocity of the barbarians combined with their fanatic zeal (typical for heretics) the Vandal kings ruthless rulers. Nevertheless, when we juxtapose the imperial legislation with the deeds of Vandals, especially with the Edict of Huneric, the only preserved legal act concerning those issues, we can explain their policy very differently. The Vandal kings quite accurately adopted and imitated the methods of combating heresy recommended in the Roman legislation. The royal officials of Roman origin and the Roman Arians, who cooperated with Vandals, were probably very well informed in that matter and could deliver the necessary “know how.” In his edict, King Huneric directly indicates the laws issued by the emperors as the basis for his legal regulations directed against the followers of the Nicene orthodoxy. A more thorough analysis of similarities can be an important contribution to research on the extensive use of the Roman administration and law in the barbarian kingdoms in the Western part of the Roman Empire.